Боксер Билли - Берроуз Эдгар Райс (Забытые шедевры приключенческой литературы, 1992)
Экземпляры: ф.1 (1995) / Инвентарный номер: 37670 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44